Electrodeposition of Zinc from 1-ethyl-3-methylimidazolium acetate-water Mixtures: Investigations on the Applicability of the Electrolyte for Zn-Air Batteries. Issue 9 (2nd June 2018) - Ghazvini, Maryam Shapouri; Pulletikurthi, Giridhar; Cui, Tong; Kuhl, Chantal; Endres, Frank
Abstract : In this paper, the influence of various concentrations of water on the electrochemical and spectroscopic behavior of 1-ethyl-3-methylimidazolium acetate ([EMIm]OAc) and of 1 M Zn(OAc)2 /[EMIm]OAc has been investigated. The results show that the added water can reduce the viscosity and improve the conductivity of the employed electrolyte. Spectroscopy results reveal that both [EMIm]OAc and 1 M Zn(OAc)2 /[EMIm]OAc interact with water and the extent of interaction varies with the amount of water. Furthermore, the electrochemical behavior of 1 M Zn(OAc)2 /[EMIm]OAc is changed with the addition of different concentrations of water. A minimum of 20 vol% water was necessary to electrodeposit Zn from 1 M Zn(OAc)2 /[EMIm]OAc at room temperature. Moreover, 1 M Zn(OAc)2 /[EMIm]OAc with 20 vol% water was assessed for its possible application as an electrolyte in a Zn-air battery.